Structural steel drafting and design - Maclaughlin, David C.; Estrada, Hector (Delmar, Cengage Learning, 2009)
Clarifies the vital interdependence between structural steel design and fabrication drawings, equipping students to work flexibly with both. This book offers an overview of structural design theory. It provides examples, illustrations, and real-world assignments